Hazardous solvent source reduction - Callahan, Michael S. (McGraw-Hill, Inc., 1995)
Solvents are widely used throughout industry for a range of cleaning activities. Given the large volume of cleaning solvents currently in use, and the regulatory pressures forcing some of these solvents out of the marketplace, industry must reassess its cleaning practices. This book details locating, testing and implementing environmentally preferred cleaning technologies.